Ocena istotności czynników opłacalności innowacyjnego projektu inwestycyjnego - Gryko, Józefa Monika (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper presents an evaluation of priority number for factors determining effectiveness of investment project. This method is based on the methodology of risk priority number evaluation in the failure mode and effect analysis (FMEA). The method presented in this paper is an expansion of sensitivity analysis. It is one of the subjective method of risk analysis and can be used especially in the evaluation of innovative project efficiency, where statistical analysis of volatility couldn't be used because of the lack of historical data and past experiences with such projects. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 78-84